The Values of Islamic Education in the Traditional Wedding Ceremony of the Karo Tribe - Barus, Ari Pramaji; Budianti, Yusnaili; Arsyad, Junaidi (Institut Agama Islam Sunan Giri (INSURI) Ponorogo, 2023)
This study aims to analyze what processions are relevant to Islamic education's values and the values of Islamic education in traditional ceremonies of the Karo tribe in Aji Baho Village, Biru-Biru District, Deli Serdang Regency. This research is qualitative with a phenomenological approach. The source of the data used is primary data collected directly by researchers, namely data obtained from informants, namely the Head of Aibaho Village, Community Leaders of Ajibaho Village, Several People of Ajibaho Village, Biru-Biru District, Deli Serdang Regency. The secondary data are village archives, records of observations, and several other documents related to research in Ajibaho village, Biru-Biru District, Deli Serdang Regency. The results of the study were. First, the procession was divided into 2, namely pre-marriage (the stage of nungkuni kata, ngembah belo selembar, nganting manuk) and the wedding procession (process rose, reconnaissance pedah-pedah / luah, prayer congratulations, traditional work perjabun singuda, belo selembar, man bersama and man sepiring) and second, the value of education in ceremonies that contain the value of tawhid, worship, morals, ukhuwah. According to the researchers' analysis, the procession and the value of education at the ceremony contain prayers, hopes for happiness, health, cheap sustenance, active effort, and obedience to worship. The value of Islamic education in the Karo tribal wedding ceremony can be seen in two processes: the premarital and when the wedding occurs.